HUBUNGAN KAWAN-LAWAN ANTARA MUSLIM DAN NON-MUSLIM: Kajian Tematik Etnografis Surah al-Mumtaá¸¥anah - Muhammad Najib (STAI AL-ANWAR SARANG, 2020)
To protect the believed fundamental values​, a country/nation commonly applies the concept of friend and foe. Likewise, what had been done by Islam in the Medina period as a country tinged with tensions often leading to wars with the people of Mecca who were considered infidels, although in other side building friendly relation with the Habasyah Christian State. The condition strengthens that the Qur’an has been providing guidance to Muslims in formulating the sorting of friends and foes. Related to this, Surah al-Mumtaḥanah verses 8 and 9 discuss the concept of friend and foe. It is on this basis that a comprehensive study of the concept needs to be conducted to find the whole view about the topic. This study uses a thematic interpretation method of the surah and the ethnographic analysis technique to explore the themes. The study concludes that the central theme of surah al-Mumtaḥanah is addressing opponents firmly and fairly, friend-foe relations are not solely based on religious differences, but also on real action, namely war and expulsion due to religious differences. The concept of friend and foe in surah al-Mumtaḥanah shows a new category of non-Muslims, namely non-Muslims who are friendly with Muslims either with or without a peace agreement.